Techno-Economic Design and Social Integration of Mobile Thermal Energy Storage (M-TES) within the Tourism Industry - Bose, Archishman; Ahmed, Mohammad Samir; Kuzeva, Denitsa Dobrinova; van Kasteren, Johannes (International Journal of Sustainable Energy Planning and Management, 2019)
Industrial facilities including power plants are potential sources of cheap and low-carbon waste heat, which is often not utilized due to lack of techno-economically viable options. The present paper is based on a case study focussing at Albena tourist resort in Bulgaria to design and develop a potential Mobile Thermal Energy Storage (M-TES) system for waste heat utilization from an existing biogas-based combined heat and power (CHP) plant. Besides techno-economics, integration of the system within existing premises, freight weight, space constraint and hotel occupancy are crucial factors. Scheduling, along with the frequency of container change determines both the economic and social viability of such a project. A conceptual system design tailored to maximize energy utilization within the given constraints has been made. Core of the system is 5 containers of 15.9 tons each, with one pulling truck for minimal visibility of the transportation and a two-day container discharge cycle. A net reduction of 558 to 885 MWh per year of electricity consumption from existing electric boilers was calculated with a payback period of 7 to 14 years based on typical summer or yearly operation of hotels. The corresponding CO2 savings was 96.7%. Hybridization with Solar Thermal Systems can provide a complete substitution of the use of traditional energy sources for domestic hot water.